Transient congenital hypothyroidism : cut off value for diagnosis, median time for normalization of thyroid function and factors affecting the median time - Hamid, Siti Hazlini Abdul Hamid (2018)
Purpose: To look into cut off value for earlier discrimination between transient and permanent hypothyroidism, to determine median time for thyroid function to normalize upon cessation of treatment in transient group and its affecting factors. Method: 55 cases of congenital hypothyroidism were identified from retrospective record reviews. 37 cases were with permanent hypothyroidism and 18 cases were with transient hypothyroidism. The optimal cut off value of initial thyroid stimulating hormone (TSH) and free thyroxine (FT4) level were analyzed using receiver operating characteristics (ROC) curve analysis for both groups. Kaplan-Meier survival analysis was conducted to estimate median time for thyroid function to normalize within the transient hypothyroidism group. The log-rank test was used to determine factors affecting the median time. Results: The cut off value for initial TSH within transient hypothyroidism group was 13.55 mIU/L with area under ROC curve of 68.9 % (sensitivity 58.8 %, specificity 73.5%) and the initial free T4 was 13.45 pmol/L with area under ROC curve of 71 % (sensitivity 70.6 %, specificity 64.7%). The median time obtained was about 8 weeks and there were no significant affecting factors identified. Conclusion: Transient hypothyroid infants’ initial TSH was lower compared to permanent group and it takes 2 months for thyroid function to normalized.